Statin use and 30‐day mortality in patients with acute symptomatic pulmonary embolism. (22nd May 2022) - Siniscalchi, Carmine; Muriel, Alfonso; Suriñach Caralt, Jose Maria; Bikdeli, Behnood; Jiménez, David; Lobo, José Luis; Amado, Cristina; Gil‐Díaz, Aída; Imbalzano, Egidio; Monreal, Manuel; ,
Abstract: Background: Statins possess antithrombotic and profibrinolytic properties. The association between statin use and short‐term outcomes in patients with acute pulmonary embolism (PE) remains unknown. Methods: We used the data from the Registro Informatizado de Pacientes con Enfermedad TromboEmbólica registry to compare the 30‐day all‐cause mortality in patients with acute PE according to the use of statins. Secondary outcome was fatal PE. We used cancer‐related mortality as a falsification endpoint. Results: From January 2009 to April 2021, 31 169 patients with PE were recruited. Of these, 5520 (18%) were using statins at baseline: low intensity: 829, moderate: 3636, high intensity: 1055. Statin users were older and had a higher frequency of diabetes, hypertension, or atherosclerotic disease than non‐users ( P <0.001 for all comparisons). During the first 30 days, 1475 patients died (fatal PE, 255). On multivariable analysis, statin users had a lower risk of all‐cause death (odds ratio [OR]: 0.65; 95% confidence interval [CI]: 0.56–0.76) and fatal PE (OR: 0.42; 95% CI: 0.28–0.62) than non‐users. The risk for death was lower in patients using either low‐ (OR: 0.51; 95% CI: 0.34–0.77), moderate‐ (OR: 0.68; 95% CI: 0.57–0.81), or high‐intensity statins (OR: 0.68; 95% CI: 0.51–0.92). Results did not change in mixed effects logistic regression models with hospitals as a random effect. Statins were not associated with a significant chance in cancer mortality (falsification endpoint). Conclusions: PE patients using statins at baseline had a significantly lower risk of dying within the first 30 days than non‐users. Randomized trials are needed to confirm these data.